In silico dietary interventions using whole-body metabolic models reveal sex-specific and differential dietary risk profiles for metabolic syndrome - Alessi, Drew S.; McCreery, Chloe V.; Zomorrodi, Ali R. (Frontiers in Physiology, 2025)
Metabolic Syndrome (MetS) is a cluster of metabolic disorders that substantially increases the risk of chronic metabolic diseases. Diet plays a crucial role in MetS progression, yet a mechanistic understanding of its impact on MetS risk remains elusive. To address this gap, we conducted a rigorous in silico diet intervention study by leveraging organ-resolved sex-specific whole-body models of metabolism. These models were utilized to computationally evaluate the effect of 12 diverse dietary regimens on key MetS biomarkers—glucose, triacylglycerol, LDL-C, HDL-C—and fatty acid beta-oxidation in representative male and female subjects. Our analyses elucidated molecular mechanisms underlying the link between conventionally unhealthy diets and elevated MetS risk. Specifically, a typical Unhealthy diet indicated elevated triacylglycerol storage in the adipocytes and increased LDL-C to HDL-C ratios across both genders. Conversely, healthier dietary patterns like the Mediterranean, Balanced, and plant-based diets promoted favorable profiles for these biomarkers. Beyond substantiating these known dietary impacts, our analysis also revealed non-intuitive responses to diet. Notably, Vegan and Vegetarian diets induced elevated fatty acid oxidation compared to high-fat regimens like the Ketogenic diet, suggesting their potential in mitigating MetS risk. In addition to these overall trends, pronounced gender differences in metabolic responses to diets were observed, highlighting the need for gender-tailored dietary recommendations. Organ-specific dietary responses and their contributions to MetS biomarkers were also delineated, pinpointing the liver and lungs as major regulators of blood glucose homeostasis. This study contributes to a deeper understanding of the intricate interactions between diet and MetS risk.